The History of the Arrival and Development of the Arab Community in Palembang: Social, Cultural Influences, and the Development of Formal Educational Institutions - Ahmad Rofiq; Choirun Niswah; Bety; Maryam; Rahmat Abdullah (Universitas Darussalam Gontor, 2025)
This study examines the significant contributions of the Arab community to the socio-religious and cultural development of Palembang, a historically rich and diverse city in Indonesia. Originating from Hadramaut, Yemen, during the era of the Palembang Darussalam Sultanate in the 17th century, the Arab community played a pivotal role in the Islamization of the region and the enrichment of local identity through cultural and social values. Their integration with the local population resulted in profound acculturation, visible in religious traditions, such as Maulid Nabi and zikr practices, and the implementation of Islamic principles in governance and daily life. This research employs a qualitative methodology with a descriptive approach. It utilizes in-depth interviews with prominent figures and descendants of the Arab community and historical document analysis. The study focuses on historical areas like Kampung Arab Al-Munawwar and Ulu-Ilir, which are central to the Arab community’s legacy in Palembang. The findings highlight the establishment of Islamic educational institutions, such as madrasahs and pesantrens, by prominent Arab figures like Habib Alwi Bahsin. These institutions became pivotal in disseminating religious and general knowledge, fostering intellectual and social empowerment. The study underscores the integration of Islamic values into local culture, evident in acculturated traditions, culinary practices, and community activities. In conclusion, the Arab community’s contributions extend beyond religious propagation, encompassing education, social development, and cultural integration. Their legacy has profoundly shaped Palembang’s identity, reinforcing its status as a vital center of Islamic civilization in the Nusantara.